(untitled) (Medical Forum Monthly, 2024)
Objective: This study was aimed to determine the prevalence of HCV, HBV and HIV in male prisoners at central jail, Karachi. Study Design: Descriptive / cross sectional study Place and Duration of Study: This study was conducted at Clinical Laboratory of Lyari General Hospital and Dow University of Health Sciences laboratory from October 2014 to Feb 2015. Materials and Methods: A selected team of doctors and para medical staff collected the blood samples from the prisoners of jail. Lab tests was performed for anti HCV and HBsAg and HIV antibodies. By rapid testing immunochromatographic (ICT) devices were used for screening. Reactive samples were retested and final diagnosis of seropositvity for HCV and HBV was made using ELISA system (enzyme linked immunosorbent assay) whereas HIV positive serum was rechecked with chromatoghraphic immunoassay. The repeated and confirmed positive sera for HCV, HIV and HBV were included in the analysis. Statistical analysis was performed using SPSS (IBM SPSS Statistics 20.0). Results: A total of 323 male prisoners were evaluated 226(69.96%) of prisoners were between 20-30 years, majority fell in age range of 31-40 years. 45(13.9%) among 323 male prisoners were found to be HEP C positive, 4(1.2%) was HEP B positive and 9(2.78%) were HIV positive. Male prisoners were highest among 20-30 years all 3 infections were more in the same age range. Overall seroprevalence of HCV coinfection with HIV or HBV or both was 6/323 (1.85%). Among total HCV positive prisoner’s evidence of co infection HCV-HIV co infection prevalence rate was (6/45) 13.3%. Conclusion: Prevalence of HCV was 14%, HBV was 1.2% and HIV was 2.78% in male prisoners of central jail.